Effects of Different Types of Feed on the Growth and Survival Rate of Betta splendens - NengTias, Resti Ayu; Watiniasih, Ni Luh; Dewi, Ayu Putu Wiweka Krisna (Advances in Tropical Biodiversity and Environmental Sciences; Vol 5 No 3 (2021): ATBES, 2021)
Betta fish ( Betta splendens ) are freshwater ornamental fish that is very popular because it’s beautiful colors and unique behavior. This study aims to determine the growth measuring weight and length as well as the survival rate of betta fish seeds by providing different types of food that was conducted in door at Tulungagung, East Java, Indonesia. The study was experimentally designed with completely randomized design consisting of 3 treatments and 4 replications. The treatments A was fed with Tubifex sp., treatment B with artificial food (pellets), and treatment C was  consisted of a combination of Tubifex sp., and artificial food. The test fish were 30 days old with a stocking density of 5/plastic bucket, where feeding was done ad-libitum . The study was conducted for 42 days. The parameters measured in this study were the growth in absolute weight and absolute length and its survival rate. Observations were analyzed using One Way Analysis of Variance (ANOVA) and further tests were carried out using the Duncan test. The results show that different feeding strategies had a significant effect on the growth of absolute weight and absolute length, and had no significant effect on the survival rate of betta fish. Water quality parameters measured include an average temperature was valued at 25.01 o C-25.87 o C, while the average pH was 8.42-8.47, and average dissolved oxygen (DO) was 4.13-4.17 mg/L.